Patterns and evolution of moral behaviour: moral dynamics in everyday life. (2nd January 2016) - Barque-Duran, Albert; Pothos, Emmanuel M.; Yearsley, James M.; Hampton, James A.
ABSTRACT: Recent research on moral dynamics (the processes and phenomena – collective or individual – by which moral behaviour and moral attitudes emerge, evolve, spread, erode or disappear) shows that an individual's ethical mind-set (i.e. outcome-based vs. rule-based) moderates the impact of an initial ethical or unethical act on the likelihood of behaving ethically on a subsequent occasion. More specifically, an outcome-based mind-set facilitates Moral Balancing (behaving ethically or unethically decreases the likelihood of engaging in the same type of behaviour again later), whereas a rule-based mind-set facilitates Moral Consistency (engaging in an ethical or unethical behaviour increases the likelihood of engaging in the same type of behaviour later on). The objective was to look at the evolution of moral choice across a series of scenarios, that is, to explore if these moral patterns (Balancing vs. Consistency) are maintained over time. The results of three studies showed that Moral Balancing is not maintained over time. On the other hand, Moral Consistency could be maintained over time, if the mind-set was reinforced before making a new moral judgment (but not otherwise).